2012
DOI: 10.1111/j.1742-1241.2012.02959.x
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-glutamyltransferase levels and risk of metabolic syndrome: a meta-analysis of prospective cohort studies

Abstract: Our results show that GGT levels are positively associated with risk of MetS independently of alcohol intake. GGT may be a promising marker for predicting MetS. Further studies are needed to confirm our findings and elucidate the underlying mechanisms in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 29 publications
6
44
0
Order By: Relevance
“…4,5,8 In addition to these conventional clinical uses, current findings emphasized that higher ALT and GGT levels and lower AST/ALT level can be biomarkers for clustering of metabolic syndrome components in adolescents. Therefore, given the evidence of ALT and GGT as predictors of elevated cardiovascular mortality and metabolic syndrome in adults [3][4][5][6] and the link of metabolic syndrome in childhood with development of metabolic syndrome, type 2 diabetes, and cardiovascular disease in adulthood, 1,2 liver enzymes could be potential indicators of predicting cardiometabolic diseases in the future.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…4,5,8 In addition to these conventional clinical uses, current findings emphasized that higher ALT and GGT levels and lower AST/ALT level can be biomarkers for clustering of metabolic syndrome components in adolescents. Therefore, given the evidence of ALT and GGT as predictors of elevated cardiovascular mortality and metabolic syndrome in adults [3][4][5][6] and the link of metabolic syndrome in childhood with development of metabolic syndrome, type 2 diabetes, and cardiovascular disease in adulthood, 1,2 liver enzymes could be potential indicators of predicting cardiometabolic diseases in the future.…”
Section: Discussionmentioning
confidence: 97%
“…2 Earlier studies in adults have found associations of metabolic syndrome and its health consequences, such as cardiovascular disease and type 2 diabetes with liver enzyme levels, surrogate markers of nonalcoholic fatty liver disease (NAFLD). [3][4][5][6][7][8] g-Glutamyltransferase (GGT), a biomarker for oxidative stress associated with glutathione regulation is closely linked with diabetes, metabolic syndrome, and cardiovascular disease. [3][4][5] Alanine aminotransferase (ALT) activities are also related with hepatic insulin resistance and predict diabetes and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13][14][15] Moreover, more than a dozen of longitudinal studies with a relatively long duration of follow-up reported that NAFLD, as diagnosed by either ultrasonography or biochemistry, is independently associated with an increased incidence of several components of metabolic syndrome, not only of T2DM. 4,[16][17][18][19][20][21][22][23][24] Amongst the prospective studies that have used ultrasonography to diagnose NAFLD and that have assessed the risk of developing T2DM, the risk of T2DM varied markedly from an approximately 60% increase to approximately a sixfold increase in risk. [7][8][9][10][11][12][13][14][15] This wide interstudy variation in T2DM risk might reflect differences in NAFLD severity, as the study by Park et al 13 showed that the incidence rate of T2DM increased sharply according to the ultrasonographic severity of NAFLD at baseline (normal, 7%; mild, 9.8%; moderate-to-severe, 17.8%).…”
Section: Does Nafld Predict the Development Of T2dm And Metabolic Synmentioning
confidence: 98%
“…87 Most of the studies were from Asian populations, and hence further studies are required to generalize the findings. A metaanalysis of 13 prospective cohort studies to evaluate the association of serum GGT activity with hypertension comparing the top GGT category with the lowest showed RR was 1.94 (CI 1.55-2.43, P < 0.001).…”
Section: Risk Factorsmentioning
confidence: 98%